2019
DOI: 10.1177/0899764019837603
|View full text |Cite
|
Sign up to set email alerts
|

Nonprofits as Schools for Democracy: The Justifications for Organizational Democracy Within Nonprofit Organizations

Abstract: Nonprofit organizations are often claimed to be schools of democracy: “that produce citizens able and ready to participate in society” (as stated by Dodge and Ospina in Nonprofits as “schools of democracy”: A comparative case study of two environmental organizations, 2016, page 479). This claim is predicated the external role nonprofits play in producing democracy, particularly by engendering civic action. In contrast, this article promotes nonprofits’ internal organizing processes to produce democracy within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…Some recent progress has been made related to the hierarchy-market axis found in the traditional economics-inspired governance literature where, for example, collective action has been highlighted as a dimension that could balance or complement this classical dichotomy when applied to nonprofit firms (Tortia and Valentinov, 2018). Along similar lines, it has often been suggested that internal democracy and democratic representation of different groups are important components in the governance of nonprofit and voluntary organizations (see, for example, Eikenberry, 2009;Enjolras and Steen-Johnsen, 2015;King and Griffin, 2019). What we are still lacking, however, is high-quality research that more directly addresses the actual role and importance of values in nonprofit governance.…”
Section: The Lacuna Of Economics Contracts and Organizational Ownershipmentioning
confidence: 98%
“…Some recent progress has been made related to the hierarchy-market axis found in the traditional economics-inspired governance literature where, for example, collective action has been highlighted as a dimension that could balance or complement this classical dichotomy when applied to nonprofit firms (Tortia and Valentinov, 2018). Along similar lines, it has often been suggested that internal democracy and democratic representation of different groups are important components in the governance of nonprofit and voluntary organizations (see, for example, Eikenberry, 2009;Enjolras and Steen-Johnsen, 2015;King and Griffin, 2019). What we are still lacking, however, is high-quality research that more directly addresses the actual role and importance of values in nonprofit governance.…”
Section: The Lacuna Of Economics Contracts and Organizational Ownershipmentioning
confidence: 98%
“…Acting as de Tocqueville's “schools of democracy,” CSOs can teach members and participants democratic practices at the organizational and community level through public‐spirited activity and open public discourses (Alexander et al., 1999), foster local participation in the development process and service provision, empower and give voice to their communities. “In the end, participants in voluntary associations are more likely to be politically active as they have obtained the skills, the network and the mindset to be so” (Van der Meer & Van Ingen, 2009, p. 282; see also King & Griffin, 2019; Rawlings, 2012). The socialization function of civil society supports participatory democracy (Eikenberry & Kluver, 2004), and this process is enhanced by CSOs that function as value‐guardians, advocates and develop social capital (Anheier & Toepler, 2023).…”
Section: Changing Perspectives On Democratization and Civil Society I...mentioning
confidence: 99%
“…Through the production of social capital, CSOs can further serve as mobilizing structures for creating social movements (Bernhard, 1993) and encouraging people to protest collectively (Boulding, 2014; Brass, 2022). Furthermore, internal organizational practices in nonprofits, such as the checks and balances between the governance and management levels as well as volunteer citizen engagement, in and of themselves, may serve as models or schools of democracy in society at large (King & Griffin, 2019; Rawlings, 2012).…”
Section: Service‐providing Csos and Democracy: Positive And Negative ...mentioning
confidence: 99%
“…Literature on civic organizations, often labeled NGOs or CSOs, ascribes to them three key roles in representative systems—developing democratic capacities among citizens, functioning as mechanisms to develop and represent interests and agendas, and acting as alternative institutions for citizen civic and political voices (Warren, 2003, 2017; also; Kuchukeeva & O’Loughlin, 2003; King & Griffin, 2019; Dodge & Ospina, 2016; Green, 2002). This literature offers evidence that civic organizations in both developed and developing contexts will enhance democratic practice via these key roles.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A strong civil society is associated with robust governing institutions and democracy (Dodge & Ospina, 2016; Green, 2002; Khambule, 2021; King & Griffin, 2019; Kuchukeeva & O’Loughlin, 2003; Warren, 2003, 2017), but how governing institutions and CSOs co‐evolve, particularly, the individual attitudinal micro‐foundations of this process, is not as well understood (Newton, 2002). While early studies of the role of civil society in democratic transitions viewed civic organizations in largely undifferentiated terms, recent research recognizes that there are different types of CSOs and that they play quite distinct roles (Toepler et al., 2020), and may, therefore, have a differential impact on democratic processes in emerging democracies and authoritarian countries.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%